KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBUATAN KEPUTUSAN DI SEKOLAH BERBASIS PESANTREN - Muhammad Khoirul Anam; Mustiningsih Mustiningsih; Raden Bambang Sumarsono (Universitas Negeri Malang, 2019)
Abstrack: This study aims to describe the types of decision-making in school-based schools, the role of principals as leaders in decision-making at boarding schools, school principals in decision-making at boarding schools and the obstacles and solutions of school principals in decision-making in school-based boarding school. The method used in this study is a qualitative approach with a type of case study research. While the procedure for collecting data in this study uses observation, interview, and documentation techniques. The results obtained from this study are: (1) the types of decisions in the boarding school-based schools are in two categories, namely the decisions of the principal and decisions of the caregiver of the foundation; (2) the role of the principal as a leader in making decision-making at the boarding school-based school is that there are two roles that are carried out, namely as the absolute decision maker in the academic field of the school and the liaison role between the school and the foundation; (3) principals' procedures for making decisions at boarding schools based on: conducting leadership meetings, carrying out draft analysis of planning, submitting to the foundation (if the decision is related to the foundation), alternative decision-making, selected alternatives, and implementing decisions; (4) the type of leadership of the principal in making decisions in boarding school-based schools is: democratic, authoritarian and familial; and (5) school principals' constraints and solutions in decision making at boarding schools based on: first, there are guidelines from foundations that narrow down the decision-making movements in schools so that when making decisions the principal always tries to be guided by the rules that have been made from foundation. Secondly, foundation decisions that are difficult to carry out on the ground and the solution to the school remains as much as possible carrying out decisions that come directly from the foundation. Third, the existence of pros and cons related to the implementation of new decisions was decided at school so that the school principal always provided information and explanations regarding the decisions recently decided on for the school. Keywords: Principal leadership, decision making, boarding school based Abstrak: Penelitian ini bertujuan untuk mendeskripsikan jenis-jenis pembuatan keputusan di sekolah berbasis peantren, peran kepala sekolah sebagai pemimpin dalam pembuataan keputusan di sekolah berbasis pesantren, prosedur kepala sekolh dalam pembuatan keputusan di sekolah berbasis pesantren serta kendala dan solusi kepala sekolah dalam pembuatan keputusan di sekolah berbasis pesantren. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis penelitian studi kasus. Sedangkan prosedur pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara, dan dokumentasi. Hasil yang diperoleh dari penelitian ini adalah: (1) jenis keputusan di sekolah berbasis pesantren itu ada dua kategori yaitu keputusan dari kepala sekolah dan keputusan dari pengasuh yayasan; (2) peran kepala sekolah sebagai pemimpin dalam pembuataan keputusan disekolah berbasis pesantren itu ada dua peran yang dilakukan yaitu sebagai pengambil keputusan mutlak dalam bidang akademik sekolah dan peran penghubung antara sekolah dengan pihak yayasan; (3) prosedur kepala sekolah dalam pembuatan keputusan di sekolah berbasis pesantren yaitu: melakukan rapat pimpinan, melakukan analisis perencanaan penyusunan konsep, pengajuan kepada pihak yayasan (apabila keputusan menyangkut dengan yayasan), alternatif pemecahan keputusan, alternatif terpilih, dan implementasi keputusan; (4) tipe kepemimpinan kepala sekolah dalam pembuatan keputusan di sekolah berbasisi pesantren adalah: demokratis, otoriter, dan kekeluargaaan; dan (5) kendala dan solusi kepala sekolah dalam pembuataan keputusan di sekolah berbasis pesantren yaitu: pertama, adanya pedoman dari yayasan yang mempersempit dalam pergerakan pembuatan keputusan di sekolah sehingga pada saat pembuatan keputusan kepala sekolah selalu berusaha berpedoman kepada aturan-aturan yang telah dibuat dari yayasan. Kedua, keputusan yayasan yang sulit dilakukan di lapangan dan solusinya sekolah tetap semaksimal mungkin menjalankan keputusan yang turun langsung dari yayasan tersebut. Ketiga, adanya pro dan kontra terkait pelaksanaan keputusan yang baru diputuskan di sekolah sehingga kepala sekolah selalu memberikan sosialisasi dan penjelasan terkait keputusan yang baru diputuskan untuk sekolah tersebut. Kata kunci: kepemimpinan kepala sekolah, pembuatan keputusan, sekolah berbasis pesantren